1999
DOI: 10.1038/12447
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of cd39/ATP diphosphohydrolase results in disordered hemostasis and thromboregulation

Abstract: CD39, or vascular adenosine triphosphate diphosphohydrolase, has been considered an important inhibitor of platelet activation. Unexpectedly, cd39-deficient mice had prolonged bleeding times with minimally perturbed coagulation parameters. Platelet interactions with injured mesenteric vasculature were considerably reduced in vivo and purified mutant platelets failed to aggregate to standard agonists in vitro. This platelet hypofunction was reversible and associated with purinergic type P2Y1 receptor desensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
530
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 523 publications
(562 citation statements)
references
References 44 publications
25
530
3
4
Order By: Relevance
“…Examples of cellular co-expression of NTPDases identified by immunocytochemistry include epithelial cells in a variety of tissues [40]. NTPDase1 is the most thoroughly investigated enzyme and considerable insight has been gained from the generation of knockout mice [41,42]. NTPDase1 is a lymphocyte activation marker and found to be expressed on natural killer cells, monocytes, dendritic cells, and subsets of activated T cells.…”
Section: General Properties and Functional Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Examples of cellular co-expression of NTPDases identified by immunocytochemistry include epithelial cells in a variety of tissues [40]. NTPDase1 is the most thoroughly investigated enzyme and considerable insight has been gained from the generation of knockout mice [41,42]. NTPDase1 is a lymphocyte activation marker and found to be expressed on natural killer cells, monocytes, dendritic cells, and subsets of activated T cells.…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…There are multiple examples showing that application of inhibitors such as the nucleotide analogue ARL 67156 potentiate nucleotide-mediated neurotransmission [170][171][172][173]. Deletion of NTPDase1 in mice revealed a key role of this enzyme in the prevention of thrombosis [41,42], in purine signaling in angiogenesis [174], vascular permeability [175,176], vascular relaxation [49], in the control of macrophage function [177], or also in promoting tumor growth [178]. Accordingly, transgenic mice expressing human NTPDase1 exhibited impaired platelet aggregation and were protected from thrombosis in a transplantation setting [179].…”
Section: Downstream Signaling Nucleotidesmentioning
confidence: 99%
“…6 CD39 is the dominant vascular endothelial and immune ectonucleotidase and hydrolyzes both ATP and ADP in the plasma to AMP, ultimately to adenosine via CD73. 6 Another NTPDase associated with the vasculature and expressed by HSC and portal fibroblasts is the cell-associated ecto-ATPase (CD39L1 or NTPDase2). 7 Extracellular nucleotides regulate inflammation and immunity via purinergic/ pyrimidinergic P2-receptors (P2X-R and -P2Y-R receptors).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that deletion of CD39 results in disordered purinergic signaling responses that compromise vascular thromboregulation, promote inflammatory responses, and impact hepatic metabolism [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%